Risk Management in Supply Chain (Managing Uncertainty in Supply Chain) - Kumar, Santosh (Digital Repository of Theses - SSBM Geneva, 2025)
Post covid, Supply chain risk management has been increasingly paid attention by most of the researchers and industrialists. Of late this has become a more popular area of research. This research proposal aims at defining supply chain management and the risks/uncertainties associated with supply chain (SCRM). This research proposal is classified into six major categories: I. Introduction of Supply chain & Risk Management, Problem statement/major challenges, Objective/purpose of research, II. Preliminary Literature review, III. Research methodology, approach & strategy, Research design, Research Study Period, Schedule, Data Collection & Research Design Limitations, IV. Survey Results, V. Discussion on Survey Results, VI. Summary & Recommendations for future Research & Conclusion. After having more than 20 years of personal experience in the supply chain & gone through all the secondary data available on Supply chain risk management, I realize that still lot of risks/uncertainties are available in this domain, which needs to be anticipated & potential solutions need to be found to lessen the impact of these risks on the business. This research will help the supply chain professionals to foresee potential risks & challenges & also be ready to deal with them.